Socio-economic and physical transformations in Iloilo City's waterfront 1855 to the post-war years - Madrid, Randy M. (Iloilo City UP Visayas, 2001)
"This paper discusses the morphogenesis of Iloilo City's waterfront from an interisland harbor in the 17th and 18th centuries to an international port catering to the growing Philippine sugar trade in the 19th and 20th centuries. The focus of the study are the various socio-economic and physical developments whcih are good references in explaining the rise of Iloilo as the "Queen City of the South" in the late 19th century and its eventual urban decline several decades later. In reality, the patterns of Iloilo's urbanization is mirrored by the events at the waterfront, and a thorough understanding of Iloilo City's history can only be achieved by a complete assessment of the absolute and relative changes that have taken place at the heart of the waterfront."
Keywords: Harbor -- Iloilo City